A Control Parameter Design Method for Hybrid Multi-Terminal HVDC System - Bingkun Li; Yuansheng Liang; Gang Wang; Haifeng Li; Xinquan Chen (IEEE Access)
To achieve better control performance, a comprehensive control parameter design method that considers economics, stability and dynamic performance is essential for hybrid multi-terminal HVDC systems. In this paper, a hierarchical model for the control system of Hybrid-MTDC is constructed and the parameters are optimized on two layers. On the system layer, using the normalization processing method, a system-layer objective function that considers both the minimum network loss and the voltage offset is formed for Hybrid-MTDC systems and solved with the proposed penalty interior point method. On the converter layer, using the state-space matrix method, a generic small-signal stability range of each control parameter can be obtained by the traversal calculation of the eigenvalues. Then, to identify the stricter stable operating region for the DC voltage controller under severe conditions, an additional stability criterion based on the mixed-potential theory is deduced, and the design-oriented boundaries are generated and added to the feasible region. Finally, within the design-oriented boundaries, a general dynamic performance evaluation function is constructed to determine the optimal control parameters. Utilizing the proposed method, a typical Hybrid-MTDC system is investigated, and experimental verifications are provided to validate the effectiveness and accuracy.